The Representation of Bias Perception in “Nocturnal Animals” Movie - Seddarassan, Sophia; Novellita Oley, Gabriel Angel; Irena, Florencia (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Over the decades, the process of communication within human kind has become inevitable. The process of synchronizing information transmits and received is a little more complex due to the disruption called miscommunication. Miscommunication could happen from misinterpretation in the meaning intended by the sender. Misinterpretation can be caused due to psychological noise that occurs during communication process. Psychological noise could refer to biases, prejudices and feelings that interfere with the accurate transmission or reception of a message. One of the movie that contains aspects bias perception is Nocturnal Animals. By using Peirce’s Semiotic Theory as the analytical method, the researcher found five out of eight elements of bias perception using Gestalt Principle theory including Similarity, Symmetry, Closure, Figure / Ground and Continuity that occurs within the ten-analytical unit (20 scenes) chosen by the researcher.